GHANA’S URBAN INFORMAL SECTOR: PERCEPTIONS, ATTITUDES AND CHALLENGES - AMOAH, MARY (IJRDO - Journal of Business Management, 2015)
There is a rising interest in the informal sector the world all over emanating from the realitythat the sector houses a greater share of the active labour force. The informal sector ofGhana’s economy is estimated to provide employment for approximately 80% of the activeworkforce. After over 50 years of independence, Ghana is struggling to grow and transformits informal sector as it still operates on rudimentary methods making the future veryprecarious. The study adopted the qualitative approach and sought to examine theperceptions, attitude as well as the realities and challenges of the urban informal sector withthe Ghana National Association of Garages (GNAG) and the National Association ofBeauticians and Hair Dressers as a case study (NABH).Findings of the study indicated that, the urban informal sectors absolves the academicallyweak or people who perceive themselves as weak academically. Perception amongst theurban informal sector is that, formal sector employment is rewarding than informal sectoremployment, operators don’t see themselves as entrepreneurs and commits a lot of errors intheir operations. This explains some of the reasons for the stunted growth and the limitedtransformation experienced in the sector. However, there is still hope or the sector if effortsare made to regularize the sector through the data capturing, encouraging the formation ofvibrant and registered associations, reorientation of the perception of the operators throughcapacity building and training whilst creating the necessary conducive micro andmacroeconomic environment for their operation.